Constitutional Adjudication - J. Tóth, Zoltán (Comparative Constitutionalism in Central Europe: Analysis on Certain Central and Eastern European Countries, 2022)
The present chapter deals with constitutional adjudication1 in eight East Central European countries (in alphabetical order: Croatia, the Czech Republic, Hungary, Poland, Romania, Serbia, Slovakia and Slovenia). It concentrates primarily on the tasks and competences of the institutions performing the function of constitutional adjudication. Constitutional adjudication is a broader concept than the activities of constitutional courts. It encompasses constitutional rights adjudication, which will be the subject of a separate chapter in this book, and all the mechanisms of constitutional adjudication that relate to the establishment and enforcement of violations of constitutional provisions. It is therefore important to note that the issue of constitutional adjudication does not extend to the proper investigation of the functioning of constitutional institutions but only to cases where someone (typically a state body) violates the provisions of the constitution, and this violation must be established and repaired by a body appointed to do so. All the CEE countries under review adopt a so-called concentrated (centralised) constitutional adjudication, which means that constitutional protection will typically be the responsibility of dedicated, separate body – the constitutional court. Other bodies in some of the legal systems under examination, however, may also provide constitutional protection. Although this chapter mentions  the competences of these other bodies, only the constitutional courts themselves will be analysed in detail – in terms of their competences and functions – due to the space available. Today, based mainly on the German model, five (plus one) typical main activities of concentrated constitutional courts function in all the CEE legal systems examined in this study: (1) norm control (both with abstract and concrete manner; (2) individual (direct) protection of fundamental rights (fundamental rights adjudication), (3) resolution of conflicts on competence; (4) adjudication regarding the functioning of the state (charges against public officers, banning of political parties etc); and (5) the adjudication on election disputes; furthermore, +1) the interpretation of the constitution in connection with all these and also as separate competence. All of this also indicates that constitutional adjudication is an activity separated (institutionally and mostly functionally) from ordinary adjudication and basically cannot be considered as the part of judicial system in the classical division of powers by Montesquieu.KEYWORDS: Constitutional adjudication, judicial review, abstract norm control, concrete norm control, judicial initiative, constitutional complaint, jurisdictional disputes, election disputes.